Atypical periprosthetic femoral fractures of the hip: characterisation of three cases. Issue 2 (December 2020) - Toro, Giuseppe; Di Fino, Ciro; De Cicco, Annalisa; Toro, Gabriella; Paoletta, Marco; Toro, Antonio; Tarantino, Umberto; Iolascon, Giovanni; Panni, Alfredo Schiavone
Introduction: Long-term use of bisphosphonates (BPs) has been associated with a specific type of tensile side femoral stress fracture known as Atypical Femoral Fracture (AFF). Theoretically periprosthetic femoral fractures (PFF) should be excluded from the diagnosis of AFF. However, emerging evidence correlates prolonged BPs use with the occurrence of a type of PFF with an atypical pattern (atypical PFF, APFF). The aim of the present study is to report 3 cases of APFF treated at a single centre. Methods: Clinical and radiographic records of PFF that occurred between January 2016 and August 2018 were retrospectively reviewed. All patients meeting the American Society for Bone and Mineral Research (ASBMR) criteria for definition of PFF were included. Management strategies for APFF and patient outcomes, including fracture healing and hip function (assessed by the Oxford Hip Score [OHS]) were collected. Results: 3 patients in the study period were identified as APFF (1 incomplete, 2 complete). All patients were females with a mean age of 83.3 years. All patients were treated with lateral plating. The application of a contralateral strut allograft resulted in fracture healing in cases of complete fractures. Mean OHS at final follow-up was 34.3. Conclusions: Despite occurring around a hip stem like PFF, APFF had peculiar clinical and radiographic features, making them more similar to AFF. Therefore, the orthopaedic surgeon should also consider the natural history and healing problems associated with AFF prior in order to choose the most appropriate management for APFF.